The effects of cold water immersion on medial gastrocnemius muscle architecture and performance post-exhaustive stretch-shortening cycle exercise - Kositsky, Adam (2017)
Cold water immersion (CWI) is a method highly used in the recovery from fatiguing exercise yet its efficacy is debated. It has been proposed that the resultant suppressed inflammation decreases pain and muscle soreness and thus improves performance. However, it has been shown that this long-term inhibition of inflammatory markers reduces adaptations to resistance training. Changes in muscle architecture have been shown after fatiguing exercise, potentially due to the increased inflammation, yet it is not currently known how these architectural parameters respond to different recovery methods, such as CWI. The aim of this study was to investigate how muscle architecture of the medial gastrocnemius (MG) and neuromuscular performance change after exhaustive stretch-shortening cycle (SSC) exercise and what effects a single CWI has on those parameters over 48 hours (48H). Male athletes (n = 11) were randomized into either a passive recovery control group (CON) or CWI. Maximal voluntary contraction (MVC) and maximal drop jump (DJ) tests were performed pre- and post-exhaustive SSC exercise on a sledge apparatus and again at 24 hours (24H) and 48H. Muscle architecture of MG was measured using ultrasonography at rest and during MVC. Kinetics and kinematics during maximal DJs were determined via two-dimensional motion analysis. MVC was reduced for CON post-exercise but was not significantly different from baseline for either group at 24H or 48H. However, MG fascicle length (FL) during MVC increased for both groups (>10%) at 24H and 48H. For both groups, rebound height from maximal DJ was lower post (~15%) and remained non-significantly reduced at 24H and 48H. Recovery of DJ rebound height performance (e.g. change from post measurements) was significant only for the CWI group. Ankle joint stiffness was lower for both groups post-exercise, with CON gradually recovering and CWI remaining decreased. In summary, exhaustive SSC exercise alters MG architecture, possibly in response to a diminished stretch reflex function. CWI may slightly enhance DJ rebound height at 48H, however it may come at the expense of a less efficient SSC function due to decreased ankle joint stiffness. Thus, after purely SSC exercise-induced fatigue, at 24H and particularly at 48H CWI may aid global performance during a single SSC task but the effects to the mechanisms of performance may not be beneficial for repeated SSC tasks. However, data from other muscles and joints are needed to confirm this.